2010
DOI: 10.1088/0031-9155/55/13/017
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of a novel method for determining depth-of-interaction in a PET scintillation crystal array using a single-ended readout by a multi-anode PMT

Abstract: PET detectors with depth-of-interaction (DOI) encoding capability allow high spatial resolution and high sensitivity to be achieved simultaneously. To obtain DOI information from a mono-layer array of scintillation crystals using a single-ended readout, the authors devised a method based on light spreading within a crystal array and performed Monte Carlo simulations with individual scintillation photon tracking to prove the concept. A scintillation crystal array model was constructed using a grid method. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Several groups have shown that depth-ofinteraction encoding with SiPM is feasible (13). Implementing the depth-of-interaction encoding methods suggested by our group (14,16,32) will also be possible using the SiPM arrays.…”
Section: Discussionmentioning
confidence: 96%
“…Several groups have shown that depth-ofinteraction encoding with SiPM is feasible (13). Implementing the depth-of-interaction encoding methods suggested by our group (14,16,32) will also be possible using the SiPM arrays.…”
Section: Discussionmentioning
confidence: 96%
“…12a) [70]. This 2D light dispersion can increase the contrast of DOI dependency along the DOI position than the 1D light dispersion.…”
Section: Continuous Doi Measurement By Single-ended Readoutmentioning
confidence: 95%
“…The data loss is especially significant if we employ flat panel photomultiplier tubes or multiple layers of scintillation crystals for depth of interaction measurement. 32,[34][35][36][37][38] The conventional iterative reconstruction methods (without TV minimization) produced considerable artifacts in the reconstructed images from the gapped sinograms. To reduce the artifacts due to gaps, we applied the TV minimization to the most commonly used iterative reconstruction methods, such as ART, OSEM, and RAMLA.…”
Section: Discussionmentioning
confidence: 99%